Thomas Jefferson and his role in American policy even in 1826 (Journal of the College of Basic Education, 2022)
Thomas Jefferson is one of the founding fathers of the United States of America, the main author of a document-American declaration of independence from the British government on July 4, 1776, and the third president of the United States of America for two consecutive terms (1801-1809). A spokesman for the Democratic leader of the missionary's principles and the greatest political thinker called the principles of the republic and human rights. At the beginning of the outbreak of the American Revolution in 1775, he was a prominent member of the Second Continental Congress representative for the state of Virginia at the time of the outbreak of the war, and was appointed governor of Virginia (1779-1781), was a diplomatic success.The study came with an introduction and three sections and a conclusion, which included the first part, which came under the title (Thomas Jefferson and his role in US policy until the year 1789) and in which we dealt with birth and upbringing cultural and political role in the American War of Independence and the position of the British unjust laws big role and participation in the second Philadelphia Conference and its contribution to the big in drafting the terms of the document the US independence and then appointed after the end of a bayonet US independence governor of Virginia and then appointed an ambassador as a representative of the US government in France. while eating the second section titled (Thomas Jefferson and his role in US policy until the year 1801) and dealt with the appointment of Thomas Jefferson as secretary of state, during the reign of George Washington and the most important problems encountered during this period, especially the problems that was contrary to the Finance Minister, Alexander Hamilton, while we dealt with in the other point is the participation of Thomas Jefferson in the US election in 1797 and won the position of Vice President John Adams. And taking the third section, titled (Thomas Jefferson and his role in US policy until the year 1826) and where we talked about the US presidential election and winning the post of president of the United States of America and the most important internal reforms, as we touched on another point to the most important during his presidency occurred a Louisiana Purchase County from France, as well as we dealt with the position of the continental blockade imposed by Britain on Europe and America, and we dealt with as well as his relationship with North African countries and the most important treaties that held them, and finally, we talked to the end of his reign and his most important works, which Cause constructing the University of Virginia.The study relied on a variety of sources of foreign books, books, Arab and Arabized, theses, encyclopedias, and some of the research published in magazines.